Biophysical regulation of vascular differentiation and assembly - Gerecht, Sharon (Biological and Medical Physics, Biomedical Engineering, 2011)
The ability to grow stem cells in the laboratory and to guide their maturation to functional cells allows us to study the underlying mechanisms that govern vasculature differentiation and assembly in health and disease. Accumulating evidence suggests that early stages of vascular growth are exquisitely tuned by biophysical cues from the microenvironment, yet the scientific understanding of such cellular environments is still in its infancy. Comprehending these processes sufficiently to manipulate them would pave the way to controlling blood vessel growth in therapeutic applications. This book assembles the works and views of experts from various disciplines to provide a unique perspective on how different aspects of its microenvironment regulate the differentiation and assembly of the vasculature. In particular, it describes recent efforts to exploit modern engineering techniques to study and manipulate various biophysical cues. Biophysical Regulation of Vascular Differentiation and Assembly provides an interdisciplinary view of vasculature regulation by various biophysical cues and presents recent advances in measuring and controlling such parameters. This book will be of interest to biologists, biophysicists and engineers who work with vascular differentiation and assembly.